Correlation between the variables collected at admission and progression to severe cases during hospitalization among patients with COVID‐19 in Chongqing. Issue 11 (9th June 2020) - Duan, Jun; Wang, Xiaohui; Chi, Jing; Chen, Hong; Bai, Linfu; Hu, Qianfang; Han, Xiaoli; Hu, Wenhui; Zhu, Linxiao; Wang, Xue; Li, You; Zhou, Chenmei; et al.
Abstract: Mortality is high among severe patients with 2019 novel coronavirus‐infected disease (COVID‐19). Early prediction of progression to severe cases is needed. We retrospectively collected patients with COVID‐19 in two hospital of Chongqing from 1st January to 29th February 2020. At admission, we collected the demographics and laboratory tests to predict whether the patient would progress to severe cases in hospitalization. Severe case was confirmed when one of the following criteria occurred: (a) dyspnea, respiratory rate ≥30 breaths/min, (b) blood oxygen saturation ≤93%, and (c) PaO2 /FiO2  ≤ 300 mm Hg. At admission, 348 mild cases were enrolled in this study. Of them, 20 (5.7%) patients progressed to severe cases after median 4.0 days (interquartile range: 2.3‐6.0). Pulmonary inflammation index, platelet counts, sodium, C‐reactive protein, prealbumin, and PaCO2 showed good distinguishing power to predict progression to severe cases (each area under the curve of receiver operating characteristics [AUC] ≥ 0.8). Age, heart rate, chlorine, alanine aminotransferase, aspartate aminotransferase, procalcitonin, creatine kinase, pH, CD3 counts, and CD4 counts showed moderate distinguishing power (each AUC between 0.7‐0.8). And potassium, creatinine, temperature, and D‐dimer showed mild distinguishing power (each AUC between 0.6‐0.7). In addition, higher C‐reactive protein was associated with shorter time to progress to severe cases ( r  = −0.62). Several easily obtained variables at admission are associated with progression to severe cases during hospitalization. These variables provide a reference for the medical staffs when they manage the patients with COVID‐19. Highlights: Pulmonary inflammation index, platelet counts, sodium, C‐reactive protein, prealbumin, and PaCO2 showed good distinguishing power to predict progression to severe cases. Pulmonary inflammation index, platelet counts, sodium, C‐reactive protein, prealbumin, and PaCO2 showed good distinguishing power to predict progression to severe cases. Potassium, creatinine, temperature, and D‐dimer showed mild distinguishing power to predict progression to severe cases.